Mussel‐Inspired Adhesive and Conductive Hydrogel with Long‐Lasting Moisture and Extreme Temperature Tolerance. (28th November 2017) - Han, Lu; Liu, Kezhi; Wang, Menghao; Wang, Kefeng; Fang, Liming; Chen, Haiting; Zhou, Jie; Lu, Xiong
Abstract: Conductive hydrogels are a promising class of materials to design bioelectronics for new technological interfaces with human body, which are required to work for a long‐term or under extreme environment. Traditional hydrogels are limited in short‐term usage under room temperature, as it is difficult to retain water under cold or hot environment. Inspired by the antifreezing/antiheating behaviors from nature, and based on mussel chemistry, an adhesive and conductive hydrogel is developed with long‐lasting moisture lock‐in capability and extreme temperature tolerance, which is formed in a binary‐solvent system composed of water and glycerol. Polydopamine (PDA)‐decorated carbon nanotubes (CNTs) are incorporated into the hydrogel, which assign conductivity to the hydrogel and serve as nanoreinforcements to enhance the mechanical properties of the hydrogel. The catechol groups on PDA and viscous glycerol endow the hydrogel with high tissue adhesiveness. Particularly, the hydrogel is thermal tolerant to maintain all the properties under extreme wide tempreature spectrum (−20 or 60 °C) or stored for a long term. In summary, this mussel‐inspired hydrogel is a promising material for self‐adhesive bioelectronics to detect biosignals in cold or hot environments, and also as a dressing to protect skin from injuries related to frostbites or burns. Abstract : A mussel‐inspired carbon‐nanotube ‐incorporated conductive hydrogel is developed, which uses glycerol–water as a binary solvent in the polymer network. Thus, the hydrogel can maintain its excellent conductivity, super toughness, and tissue‐adhesiveness at extreme temperature. The hydrogel may be a promising material for flexible bioelectronics survival under harsh environments.